POLYMERS IN CARDIOVASCULAR SURGERY - Matarneh, Rami; Sotnik, Svitlana; Lyashenko, Vyacheslav (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Surgical intervention is still one of the most important treatment methods to investigate or treat a pathological condition, and the cardiovascular surgery is considered one of the most important types of surgical interventions at all. The uniqueness of a human body and the impossibility of its full procreation, enforces the use of various auxiliary materials such as polymers to carry out the most difficult surgery while ensuring further vital activity. In this paper, we explore the features of polymers which are used in cardiovascular surgery, discussing the existing variety of such polymers and the orientations of their use. Depending on the carried out analysis, the classification of main types of polymers had been offered which are the most suitable for cardiovascular surgery, besides generalized classification of polymeric products defects. The obtained results enable to immediately identify all significant factors that may lead to emergence defect for the purpose of its control and prevention to improve the quality of surgical intervention and stabilize the patient’s cardiovascular system.